Clinical spectrum of premature sexual developments in a tertiary care center of South India - G., Durai Arasan; J., Hemachitra (International Journal of Contemporary Pediatrics, 2016)
Background:The clinical spectrum of precocious sexual development and its etiology are varied and we need to know our own data regarding this. The objective of the study was to study the clinical spectrum of premature sexual developments and the usefulness of imaging modalities in understanding the ongoing insult. Methods: Female child of less than 8 years of age and male child of less than 9 years of age with development of secondary sexual characteristics were registered and analyzed. After through clinical examination the children were subjected to investigations, which included radiological and hormonal. Results:Majority of cases 54% (14 cases) had symptoms before 2 years of age. Premature thelarche was seen in 58% and the majority 71% was less than 2 years of age. 17% of the female children with sexual precocity had true precocious puberty. Hypothyroidism as a cause of true precocious puberty is 8%. Heterosexual precocious puberty was seen in 16%. Among male children peripheral cause of isosexual precocious puberty was seen in two cases. Congenital adrenal hyperplasia as a cause of sexual precocity among both sexes was seen in 15%. All four children (100%) with true precocious puberty showed uterine length of > 3.5 cm and 93% of the children with isolated premature thelarche showed a uterine length of < 3.5 cm. Conclusions:Sexual precocity is most common among female children. Isolated premature thelarche is the most common type of sexual precocity. Ultrasound visualized uterine length helps in the differentiation of isosexual precocious puberty and isolated premature.